Adjuvant intraperitoneal ceftriaxone in the treatment of septic peritonitis in horses. (31st March 2020) - de Moura Alonso, Juliana; dos Santos Rosa, Gustavo; Santos, Bruna; Guerra, Simony; Ribeiro, Márcio; Watanabe, Marcos Jun; Alves, A; Rodrigues, Celso; Takahira, Regina Kiomi; Hussni, Carlos Alberto
Abstract : Background: Intraperitoneal administration of ceftriaxone maintains therapeutic abdominal concentrations for 24 hours in healthy horses. Therefore, it is a possible treatment for septic peritonitis. The aim of this study was to evaluate the efficacy of ceftriaxone as an adjuvant treatment in horses with septic peritonitis. Methods: Twenty‐six horses with clinical signs, sonography and/or laboratory findings of septic peritonitis were included. Peritoneal fluid was collected for microbiological culture and in vitro microbial sensitivity profile assessment. Daily intraperitoneal administration of ceftriaxone (25 mg/kg) was initiated with supportive and systemic antimicrobial treatment. The animals were divided into three groups: group 1—gastrointestinal tract injuries and abdominal surgery (excluding perforations/ruptures); group 2—not related to changes in the gastrointestinal tract; group 3—secondary to intestinal rupture and/or faeces contamination. Results: The mean success rate of the treatment was 77 per cent (20/26 animals), with success rates of 84.6 per cent in group 1; 87.5 per cent, group 2; and 40 per cent, group 3. Conclusions: This is the first study to report adjuvant intraperitoneal treatment ceftriaxone for septic peritonitis in horses and indicates that this treatment can successfully treat septic peritonitis in horses.